Embracing and resisting climate identities in the Australian press: sceptics, scientists and politics - Jaspal, Rusi; Nerlich, Brigitte; Van Vuuren, Kitty (Sage, 2015)
This article charts the development of a label that appeared early on in Australian debates on climate change, namely ‘greenhouse sceptics’. We explore who uses the label, for what purposes and with which effects, and how this label may contribute to the development of social representations in the climate debate. Our findings show that over the last 25 years, ‘greenhouse sceptic’ has been used by journalists and climate scientists to negativize those criticizing mainstream climate science, but that it has also been used, even embraced, by Australian climate sceptics to label themselves in order to construct a positive identity modelled on celebrity sceptics in the United States. We found that the label was grounded in religious metaphors that frame mainstream science as a catastrophist and alarmist religious cult. Overall, this article provides detailed insights into the genealogy of climate scepticism in a particular cultural and historical context.